ANALISIS INDEKS GLIKEMIK DAN KANDUNGAN GIZI SERTA UJI DAYA TERIMA MI DARI BERAS MERAH DENGAN PENAMBAHAN UMBI GARUT - Rani Gavrila; Evawany Y Aritonang; Etti Sudaryati (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
Red rice and arrowroot are functional foods that have great benefits, but the level of awareness and consumption remains low. This food can be processed into noodles, one of the more preferred foods. In this study apply the concept of glycemic index that emphasizes the importance of choosing the right foods to improve and maintain health based on the speed of rising blood sugar levels. Type of research is experiment. The acceptability test with organoleptic test to see the panelist’s preference level against the test food. Subjects in the acceptability test amount to 30 people and 8 volunteers to glycemic index analysis. The glycemic index is calculated by comparing the area under the food test curve with reference food. The object of this research is the noodles from red rice (50% red rice flour, 50% flour), noodles from arrowroot (15% arrowroot flour, 85% flour), noodles from red rice and arrowroot (35% red rice flour, 15% arrowroot flour, 50% flour). Nutritional content seen include carbohydrate, protein, fat and coarse fiber.The glycemic index values ​​of the three test food are in low category where the lowest is the red rice noodle 25,39%, arrowroot noodle 36,26% and red rice and arrowroot noodle 33%. Arrowroot noodle contains the highest 91.40% carbohydrate and 5.3% protein, the lowest fat 2.33% in red rice noodle and the highest coarse fiber found in red rice and arrowroot noodle 0.75%. Result of organoleptic test, panelist like red rice and arrowroot noodle the most in aroma, flavor and texture indicator of which each have score 67,7%, 65,5%, 68,8% with likes criteria, while for color panelist like arrowroot noodle the most that have score of 66.5% with likes criteria. The resulting noodles can be an alternative for staple foods. Red rice noodle can be recommended for diabetics, while red rice and arrowroot noodle can be consumed in society because it has the highest score in the acceptability test. Keywords: Red Rice, Arrowroot, Noodles, Glycemic Index, The Acceptability, Nutrition Content.